#1**+1 **

Looks like you know HOW to solve it, you just made a small mistake....

See that '1' on the right side of the equation? It needs to be multiplied by (n+1)(n+8) also....then compute....

Let me know if ya need more help....

ElectricPavlov Dec 18, 2019

#2**+2 **

Solve for n:

(n + 5)/(n + 8) = 6/(n + 1) + 1

Bring 6/(n + 1) + 1 together using the common denominator n + 1:

(n + 5)/(n + 8) = (n + 7)/(n + 1)

Cross multiply:

(n + 1) (n + 5) = (n + 7) (n + 8)

Expand out terms of the left hand side:

n^2 + 6 n + 5 = (n + 7) (n + 8)

Expand out terms of the right hand side:

n^2 + 6 n + 5 = n^2 + 15 n + 56

Subtract n^2 + 15 n + 56 from both sides:

-9 n - 51 = 0

Factor constant terms from the left hand side:

-3 (3 n + 17) = 0

Divide both sides by -3:

3 n + 17 = 0

Subtract 17 from both sides:

3 n = -17

Divide both sides by 3:

**n = -17/3**

Guest Dec 18, 2019